(untitled) (International Journal of Engineering and Computer Science, 2013)
Large Swarms of Intelligent Robots can be used for a wide range of tasks. There exists a plethora of challenging applications in swarm robotics and they are emerging with technology and time. Swarm Robotics is a rapidly developing new emerging technology. Swarm Robotics has potential for a variety of challenging applications ranging from military environment, disaster relief, health care and other commercial applications. This paper deals with related domains of Swarm Robotics, their comparison and various emerging and challenging applications.